Synthesis, Characterization and Antibacterial Screening of New 1-Aminoanthraquinone Derivatives - Khan, Ayad Kareem; Essa, Hayder Jafer; Al-Majidi, Suaad M H (Al-Nahrain Journal of Science, 2018)
This research includes the synthesis of new heterocyclic derivatives of 1-aminoanthraquinone bearing 2-aminobenzothaizole moieties.Substituted 2-aminobenzothiazole obtained from the reaction of 4-substituted aniline with ammonium thiocyanate in bromine and glacial acetic acid. Then these derivatives were used to prepare of 2-(2-chloroacetylamino)-6-substituted benzothiazole compounds (1-6) by treating with chloroacetyl chloride in chloroform. Refluxing these compounds with 1-aminoanthraquinoe in absolute ethanol gave N-[(2-(2-Acetamido)-6-substituted benzothiazole-2-yl]-1-aminoanthraqiunone compounds (7-12). The characterizations of all synthesized compounds were confirmed by their melting points, and FTIR, 1HNMR, 13CNMR spectroscopy.Some of the new prepared compounds were evaluated for the antibacterial activity screening against two types of Gram positive bacteria including (Streptococcuss pneumoniae, Enterococcus faecalis) and two types of Gram negative bacteria including (Salmonella typhi., Acinetobacte sp.) and compared with ceftriaxone was used as standard drugs. The results showed that most of the tasted compounds have well to moderate biological activity against the mentioned organisms compared with standard drug above.